MR-Guided Focused Ultrasound in Fibroid Treatment – Results of the 4th Radiological-Gynecological Expert Meeting - Kröncke, Thomas; David, Matthias (Geburtshilfe und Frauenheilkunde, 2019)
Magnetic Resonance-guided focused ultrasound (MRgFUS; Syn.: HIFU = high intensity focused ultrasound) is a safe and effective thermoablative technique to treat fibroid-related symptoms. The evidence is limited due to a lack of randomized trials. The indication for treatment by MRgFUS are symptomatic uterine fibroids. This consensus paper covers criteria to measure success, contraindications, side effects and complications of MRgFUS treatment. The role of MRgFUS in the setting of family planning is part of this publication.Der Magnetresonanz-geführte fokussierte Ultraschall (MRgFUS; Syn.: HIFU = hochintensiver fokussierter Ultraschall) ist ein sicheres und effektives thermoablatives Verfahren zur Behandlung myombedingter Beschwerden. Die Datenlage zum MRgFUS ist aufgrund des Fehlens randomisierter Studien limitiert. Indikation für eine Behandlung mit MRgFUS ist ein symptomatischer Uterus myomatosus. Das Konsensuspapier behandelt Erfolgskriterien, Kontraindikationen, Nebenwirkungen und Komplikationen der MRgFUS-Behandlung. Eingegangen wird auch auf die Anwendung von MRgFUS im Rahmen der Kinderwunschbehandlung.
Keywords: uterus; leiomyoma; MR-guided focused ultrasound; HIFU